For the independence of Spain, for liberty, for the republic, union of all Spaniards - Ibárruri, Dolores, 1895-1989 (Madrid : Communist Party of Spain, 1938)
1938 SA14-038-035 76 pages ; 15 cm. 15X/2/382/1